Decrease in the Patrimonial Wealth and Cultural Experience of Guayaquil, Ecuador - Ramírez Aguilar, Derly Tamara; Revilla Espinoza, Maytte Ivonne (Artes: Architecture, Technology and Sustainability, 2023)
La decrease of cultural wealth and cultural experience in Guayaquil, Ecuador, is a concerning issue that has led to the loss of essential elements of the city's identity and deeply rooted traditions. Throughout the years, Guayaquil has been an emblem of cultural diversity and heritage richness, but lately, a shadow of concern hovers over the city due to the decline of its cultural legacy. The article emphasizes the importance of preserving and revitalizing Guayaquil's cultural heritage to enrich social life, community cohesion, and boost the city's touristic appeal. There is a recognized need to connect the existing cultural nodes in Guayaquil, such as museums, theaters, and iconic public spaces, to create an integrated and accessible cultural experience for both residents and visitors. The methodology applied in the article includes an analysis of the city's cultural and urban context, along with an urban approach based on Jan Gehl's "Six Steps to Transform Public Space." Based on this methodology, strategies are proposed to counteract this cultural decline. Among these strategies is the creation of a cultural route that connects and promotes Guayaquil's cultural nodes, revitalizing urban spaces and encouraging citizen participation. Additionally, the installation of urban furniture and green areas is suggested. Through these actions, the goal is to ensure that Guayaquil's cultural legacy endures over time and enriches the lives of both Guayaquileños and visitors.
Keywords: Culture; Experience; Connection; Heritage; Nodes; Analysis